W.A. Milliken and John J. Vertrees (Editors), Code of Tennessee, Being a Compilation of the Statute Laws of the State of Tennessee, of a General Nature, in Force June 1, 1884, 1060-61 (1884), § 5533 - (:unkn) unknown (My University, 1879)
Made the sale, offer of sale, or importation into the state belt pistols, pocket pistols, revolver, or any other kind of pistols except Army or Navy pistols a misdemeanor.
Keywords: COMMERCIAL SALES REGULATION